Cover Picture: Femtosecond Stimulated Raman Spectroscopy (ChemPhysChem 9/2016). Issue 9 (20th April 2016) - Dietze, Daniel R.; Mathies, Richard A.
Abstract : The Front Cover picture sketches the first step in vision, the trans ‐to‐ cis isomerization of retinal. This not only represents one of the most important experiments conducted to date using femtosecond stimulated Raman spectroscopy, but also beautifully illustrates the capabilities of this technology. More information can be found in the Review by D. R. Dietze and R. A. Mathies onpage 1224 in Issue 9, 2016 (DOI:10.1002/cphc.201600104 ).